1992
DOI: 10.1111/j.1464-5491.1992.tb01816.x
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of a Low Glycaemic Index Diet in Type 2 Diabetes

Abstract: Low glycaemic index foods produce low blood glucose and insulin responses in normal subjects, and improve blood glucose control in Type 1 and well-controlled Type 2 diabetic patients. We studied the effects of a low glycaemic index diet in 15 Type 2 diabetic patients with a mean fasting blood glucose of 9.5 mmol l-1 using a randomized, crossover design. Patients were given pre-weighed diets (59% energy as carbohydrate, 21% fat, and 24 g 1000-kcal-1 dietary fibre) for two 2-week periods, with a diet glycaemic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
122
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(128 citation statements)
references
References 45 publications
5
122
0
1
Order By: Relevance
“…The use of low GI staple foods to form the basic and major component of each meal offers bene®ts with lipid reduction (Wolever et al, 1992) and improvements in glycaemic control (Frost et al, 1994;Fontvieille et al, 1992;Brand et al, 1991). The GI of a food is affected by the rate of digestion and absorption of the carbohydrate present in the food (Hermansen, 1994).…”
Section: Glycaemic Indexmentioning
confidence: 99%
“…The use of low GI staple foods to form the basic and major component of each meal offers bene®ts with lipid reduction (Wolever et al, 1992) and improvements in glycaemic control (Frost et al, 1994;Fontvieille et al, 1992;Brand et al, 1991). The GI of a food is affected by the rate of digestion and absorption of the carbohydrate present in the food (Hermansen, 1994).…”
Section: Glycaemic Indexmentioning
confidence: 99%
“…A low-GI diet may improve management of diabetes by lowering early postprandial hyperglycaemi and decreasing risk for postabsorptive hypoglycaemia (Brand et al, 1991;Wolever et al, 1992;Järvi et al, 1995;Gilbertson et al, 2001). By inducing low insulin levels (Björck et al, 2000) and increased insulin sensitivity (Wolever et al, 1992;Frost et al, 1996Frost et al, , 1998Järvi et al, 1999) a low-GI diet also affects the risk for other metabolic diseases associated with the insulin resistance syndrome, for example, cardiovascular disease (Wannamethee et al, 2005). A recent examination of the Framingham Offspring Study showed that diets with lower GI are associated with lower insulin resistance, and a reduced risk of developing the insulin resistance syndrome (McKeown et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Many factors such as food form, particle size, cooking, processing and starch structure affect the GI (Björck et al, 1994). There is evidence that low GI foods improve blood glucose control in people with diabetes Wolever et al, 1992a;Frost et al, 1994;Järvi et al, 1999;Gilbertson et al, 2001), reduce serum lipids in people with hypertriglyceridaemia (Jenkins et al, 1987a), prolong endurance during physical activity (Thomas et al, 1991), improve insulin sensitivity (Frost et al, 1998) and increase colonic fermentation (Jenkins et al, 1987b;Wolever et al, 1992b). In addition, low GI foods are associated with high HDL cholesterol (Frost et al, 1999) and reduced risk for developing diabetes (Salmeró n et al, 1997a,b) and cardiovascular disease (Liu et al, 2000).…”
Section: Introductionmentioning
confidence: 99%